Possibilities and prospects of conservative therapy for endometriosis, as a chronical progressing disease (review of literature) - Tatyana Yu. Pestrikova; Elena A. Yurasova; Igor V. Yurasov (IP Berlin A.V., 2020)
Relevance. Endometriosis is a common gynecological disease that affects up to 10% of women of reproductive age worldwide and is the main cause of pain and infertility. Endometriosis is a disease, although it has been known for a long time, nevertheless, in many ways it represents terra incognita for modern medicine. Aim. Analysis of literature on the feasibility of long-term and the use of the drug dienogest 2 mg (Vizanne), which has a positive effect on the quality of life of patients with endometriosis. Materials and methods. To write this review, a search was made for domestic and foreign publications in Russian and international search engines (PubMed, eLibrary, etc.) over the past 13 years. The review included articles from peer-reviewed literature. Results. The review presents data on the difficulties of verifying the diagnosis of endometriosis due to a combination of this pathology with pain, infertility, abnormal uterine bleeding. The pathogenesis of the origin of endometriosis-associated pain is presented. The efficacy of the use of the drug dienogest (Vizanne), which has a powerful antiproliferative effect that reduces the main symptoms of endometriosis (pain, bleeding), is substantiated. The expediency of long-term and safe use of the drug dienogest (Vizanne), which has a positive effect on the quality of life of patients with endometriosis, has been proved. Conclusions. Numerous scientific publications confirm the feasibility of prolonged use of the drug dienogest (Vizanne), to achieve remission during endometriosis.